Improving the efficiency of electric power transmission lines - Ayat S.Hasan; jasim, Ali k.; Rasheed , Asmaa m. (International Journal of Psychosocial Rehabilitation, 2020)
he electrical transmission lines transfer the electrical power from one place to another. The main component of the air transmission line is the conductor. The rest of the parts are auxiliary parts to carry the conductor or to isolate the conductor from the ground. In overhead lines, open, non-insulated conductors are used, and the air is the insulator between the conductors, each other along the line path. Therefore, the overhead lines are called. The conductor is the main part of the transmission line as it is the carrier that transfers electrical energy from one place to another and the conductors used in transmission lines are often exposed, i.e. not covered by an insulating material and are suspended between poles or towers that are far from each other distances that may reach more sometimes From 250 meters, this distance is known as the tower or sea wire.